Blue lighting decreases the amount of food consumed in men, but not in women. (1st February 2015) - Cho, Sungeun; Han, Ashley; Taylor, Michael H.; Huck, Alexandria C.; Mishler, Amanda M.; Mattal, Kyle L.; Barker, Caleb A.; Seo, Han-Seok
Highlights: Color of lighting can modulate the amount of food consumed. Blue lighting decreased the meal size in men, but not in women. Color of lighting did not affect flavor intensity and food acceptance. Abstract: Previous research has demonstrated that colors of lighting can modulate participants' motivation to consume the food placed under the lighting. This study was designed to determine whether the colors of lighting can affect the amount of food consumed, in addition to sensory perception of the food. The influence of lighting color was also compared between men and women. One-hundred twelve participants (62 men and 50 women) were asked to consume a breakfast meal (omelets and mini-pancakes) under one of three different lighting colors: white, yellow, and blue. During the test, hedonic impression of the food's appearance, willingness to eat, overall flavor intensity and overall impression of the food, and meal size (i.e., the amount of food consumed) were measured. Blue lighting decreased the hedonic impression of the food's appearance, but not the willingness to eat, compared to yellow and white lighting conditions. The blue lighting significantly decreased the amount consumed in men, but not in women, compared to yellow and white lighting conditions. Overall flavor intensity and overall impression of the food were not significantly different among the three lighting colors. In conclusion, this study provides empirical evidence that the color of lighting can modulate the meal size. In particular, blue lighting can decrease the amount of food eaten in men without reducing their acceptability of the food.